A new species of the genus Apatenia (Coleoptera: Anthribidae) from Madagascar with notes on female genitalia, redescription of the female of Apatenia quadristigma Frieser and list of Madagascan species - Trýzna, Miloš; Baňař, Petr (Zootaxa, 2013)
A new species, Apatenia stysi Trýzna & Baňař sp. nov. (Anthribidae: Anthribinae: Corrhecerini), from north-west Mad-agascar is described and the female allotype of Apatenia quadristigma Frieser, 1981 is redescribed. Female genitalia of A. stysi sp. nov. are studied and illustrated.